The Patent fact about Alcohol and Getting Stroke: A Case Control Study - Kuntalkumar H Patel; Shreyashkumar Gandhi; Dhruti Vaidya (Indian Association of Preventive and Social Medicine, 2021)
Introduction: Globally 17.9 million people die each year from CVDs (Cardio Vascular Diseases) and 85% of all CVD deaths are due to heart attacks and strokes. According to the World Health Organization (WHO), 15 million people worldwide suffer from stroke every year and after ischemic heart disease, stroke is the second most leading cause of death. Objective: To study alcohol consumption as a risk factor in patients with acute strokes. Method: Case control study was conducted among 148 newly diagnosed cases of CT scan / MRI-confirmed stroke and 148 non-stroke controls attending the tertiary hospital of central Gujarat. Sample size calculation was done, assuming the power ratio of the number of controls same as numbers of cases i.e.,1:1, specifying values for two-sided confidence level=95% (error=5%), power of study=80%, odd ratio=2.15, percent of cases with exposure=82% and percent of controls with exposure=68%. Patients who are willing to participate in the study were included. The data were analyzed using the EPI INFO TM 7.0.8.0 software. Results: Out of the total 148 cases, 100 (67.56 per cent) were male and 48 (32.43 per cent) were female. The odds of getting stroke among alcoholic was two times more as compared to non-alcoholic patients. Heavy alcohol drinkers have a significant association. Conclusion: According to the study results male married patients who drank heavily had a higher risk of stroke than light/moderate alcoholics.